Intrusion Detection and Prevention Systems in Wireless Networks - Al-Shourbaji, Ibrahim; Al-Janabi, Samaher (Kurdistan Journal of Applied Research, 2017)
In society today, public and personal communication are often carried out through wireless technology. These technologies can be vulnerable to various types of attacks. Attackers can access the signal to listen or to cause more damage on the wireless networks. Intrusion Detection and Prevention System (IDPS) technology can be used to monitor and analyze the signal for any infiltration to prevent interception or other malicious intrusion. An overview description of IDPSs and their core functions, the primary types of intrusion detection mechanisms, and the limitations of IDPSs are discussed. This work perceives the requirements of developing new and sophisticated detection and prevention methods based on, and managed by, combining smart techniques including machine learning, data mining, and game theory along with risk analysis and assessment techniques. This assists wireless networks toremain secure and aids system administrators to effectively monitor their systems.